2013
DOI: 10.1186/1465-9921-14-110
|View full text |Cite
|
Sign up to set email alerts
|

Airway hyperresponsiveness is associated with airway remodeling but not inflammation in aging Cav1 -/- mice

Abstract: BackgroundAirway inflammation and airway remodeling are the key contributors to airway hyperresponsiveness (AHR), a characteristic feature of asthma. Both processes are regulated by Transforming Growth Factor (TGF)-β. Caveolin 1 (Cav1) is a membrane bound protein that binds to a variety of receptor and signaling proteins, including the TGF-β receptors. We hypothesized that caveolin-1 deficiency promotes structural alterations of the airways that develop with age will predispose to an increased response to alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…It is suggested that frequent asthma exacerbations evoke an airway injury-repair cycle that promotes sustained AHR by altering the structure and function of ASM cells (13,14). In addition, recent literature suggests an uncoupling of airway inflammation and AHR in asthma (9,11,15,16). Understandably, the link between injury-repair responses and AHR remains unclear.…”
Section: Airway Remodeling and Ahr: A Direct Relation?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that frequent asthma exacerbations evoke an airway injury-repair cycle that promotes sustained AHR by altering the structure and function of ASM cells (13,14). In addition, recent literature suggests an uncoupling of airway inflammation and AHR in asthma (9,11,15,16). Understandably, the link between injury-repair responses and AHR remains unclear.…”
Section: Airway Remodeling and Ahr: A Direct Relation?mentioning
confidence: 99%
“…The mechanisms by which each exacerbates the other, or whether a direct connection exists between the two, remain highly debated. Although it is suggested that airway inflammation precedes the development of both pathologies (9,10), airway structural alterations may also independently modify AHR (11,12). It is suggested that frequent asthma exacerbations evoke an airway injury-repair cycle that promotes sustained AHR by altering the structure and function of ASM cells (13,14).…”
Section: Airway Remodeling and Ahr: A Direct Relation?mentioning
confidence: 99%
“…These studies revealed that loss of Cav impairs diverse cellular signaling processes, thus subsequently genetically modified animals develop mainly organ disorders such as cardiac hypertrophy and pulmonary remodeling. These effects are prominent as the mice aged, also suggesting the cumulative effect of malfunction by caveolae (69,94,122). Endothelial reintroduction of Cav-1 largely rescued cardiac abnormality found in the Cav-1-deficient mice, and indicated the cell-specific importance of Cav function.…”
Section: Perspectivesmentioning
confidence: 83%
“…37 Multiple in vitro studies have demonstrated that infl ammation and remodeling can be dissociated and studied separately in models of disease. 38,39 Tschumperlin et al 10 showed that EGFR activation in response to bronchoconstriction can be achieved in naïve animals not previously exposed to allergen; similarly, using naive guinea pig precision cut lung slices, Oenema et al 4 demonstrated that bronchoconstriction induced by methacholine and histamine was suffi cient to enhance the expression of smooth muscle-specifi c marker proteins in the large and small airways. Th is involved a mechanism similar to that reported by Tatler et al, 26 including the release of bioactive TGF-b .…”
mentioning
confidence: 97%